ANALYSIS OF DETERMINANTS OF DIFFERENCES IN AVERAGE LENGTH OF SCHOOLING FOR BOYS AND WOMEN IN A FAMILY IN NUSA PENIDA DISTRICT - Ni Luh Ellia Chandra Dewi; Ni Made Tisnawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Unequal education between men and women causes inequality invarious job sectors, positions, roles in society. Bali is one of the provinces in Indonesia which has the highest difference in average length of schooling (RLS) for men and women. The highest RLS difference value is in Klungkung Regency. Nusa Penida District was chosen to represent the gap. The research design in the research is a quantitative approach in the form of an associative approach. This research's analytical method uses moderated regression analysis. This research uses purposive and accidental sampling techniques. The data source comes from a questionnaire with a sample of 68 families with the criteria for families living in Nusa Penida District who have at least one son and one daughter aged 18 years and over. The results of this research show that: (1) Father's education, mother's education, number of dependents, family income, and patriarchal culture simultaneously have a significant effect on the difference in average length of schooling between men and women in a family in Nusa Penida District. (2) Father's education has a positive and significant effect, mother's education has a negative and insignificant effect, number of dependents has a positive and significant effect, family income has a negative and significant effect, patriarchal culture has a positive and significant effect on the difference in average years of schooling between men and women in a family in Nusa Penida District. (3) Patriarchal culture weakens the influence of father's education, patriarchal culture strengthens mother's education, patriarchal culture weakens family income on the difference in average length of schooling between men and women in a family in Nusa Penida District.